Recent Trends in Curcumin-Containing Inorganic-Based Nanoparticles Intended for In Vivo Cancer Therapy - Douglas Dourado; Júlio Abreu Miranda; Matheus Cardoso de Oliveira; Danielle Teixeira Freire; Francisco Humberto Xavier-Júnior; Edgar Julian Paredes-Gamero; Éverton do Nascimento Alencar (MDPI AG, 2024)
Curcumin is a natural compound that has been widely investigated thanks to its various biological properties, including antiproliferative. This molecule acts on different cancers such as lung, breast, pancreatic, colorectal, etc. However, the bioactive actions of curcumin have limitations when its physicochemical properties compromise its pharmacological potential. As a therapeutic strategy against cancer, curcumin has been associated with inorganic nanoparticles. These nanocarriers are capable of delivering curcumin and offering physicochemical properties that synergistically enhance anticancer properties. This review highlights the different types of curcumin-based inorganic nanoparticles and discusses their physicochemical properties and in vivo anticancer activity in different models of cancer.